2011
DOI: 10.1152/ajpendo.00459.2010
|View full text |Cite
|
Sign up to set email alerts
|

Promoter characterization and role of CRE in the basal transcription of the rat SNAT2 gene

Abstract: Small neutral amino acid transporter 2 (SNAT2) is the most abundant and ubiquitous transporter for zwitterionic short-chain amino acids. The activity of this amino acid transporter is stimulated in vivo or in vitro by glucagon or cAMP analogs. However, it is not known whether the increase in activity at the protein level is due to an increase in SNAT2 gene transcription. Thus, the aim of the present work was to study whether cAMP was able to stimulate SNAT2 gene expression and to localize and characterize the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Urea nitrogen also increased, suggesting that glucagon may indirectly regulate amino acid levels through regulation of gluconeogenesis [224]. In agreement with this notion, glucagon also increases transcription of Sodium-neutral amino acid transporter SNAT2 in hepatocytes through a cAMP response element in the promoter region [225]. …”
Section: Systemic Amino Acid Homeostasismentioning
confidence: 87%
“…Urea nitrogen also increased, suggesting that glucagon may indirectly regulate amino acid levels through regulation of gluconeogenesis [224]. In agreement with this notion, glucagon also increases transcription of Sodium-neutral amino acid transporter SNAT2 in hepatocytes through a cAMP response element in the promoter region [225]. …”
Section: Systemic Amino Acid Homeostasismentioning
confidence: 87%
“…For SNAT2, a regulation by amino acid deprivation has been described and the mechanism linked to the presence in the first intron of a amino acid response element (AARE) acting as enhancer (Palii et al, 2004). Moreover, in liver SNAT2 is up-regulated by glucagon (Ortiz et al, 2011). For SNAT3 a regulation by PKC has been reported and linked to the glutamate/GABA-glutamine of the central nervous system.…”
Section: Slc38: Snatsmentioning
confidence: 99%
“…Therefore, the supply of amino acids is significantly increased when rats consumed a high protein diet as has been previously reported [33]. It has been demonstrated that an increase in the amount of dietary protein, stimulates the serum glucagon levels, which in turn upregulates the expression of SNAT2 via PKA in the liver, since the SNAT2 promoter gene contains a cAMP response element (CRE) at −48 bp [30].…”
Section: Discussionmentioning
confidence: 79%
“…Our results also demonstrated that the dietary protein/carbohydrate ratio influences the serum prolactin concentration. This may imply that the reduction of prolactin decreases SNAT2 expression or that the dietary protein/carbohydrate ratio can directly modulate the expression of this gene possibly via cAMP, as has been reported in the liver [30]. Further studies are needed to dissect this mechanism.…”
Section: Discussionmentioning
confidence: 91%